Survey Report Analysis on Parasitic and Microbial Quality of Laboratory Animals in Sichuan Province, 2017-2023 - LIU Lida; CHEN Bing; XIE Na; LIU Li; ZHUANG Siqi; ZOU Yixing (Shiyan dongwu yu bijiao yixue)
ObjectiveTo provide reference for further strengthening the management of laboratory animals in Sichuan Province by reviewing and analyzing the results of parasitic and microbial quality inspections of laboratory animals from 2017 to 2023. Methods Sichuan Province has 31 licensed laboratory animal production units, with the main species including mice, rats, guinea pigs, rabbits, dogs, monkeys, and pigs. Sampling inspections and reports were conducted for units with laboratory animal production qualifications in accordance with current national and local standards for laboratory animal classification. The quality inspection results for various laboratory animals in Sichuan Province from 2017 to 2023 were analyzed. Results With the exception of 2018, annual quality inspections of laboratory animals were conducted every year between 2017 and 2023. Mice: In 2017, positive results for helminths, flagellates, Salmonella, murine hepatitis virus antibodies, and murine pneumonia virus antibodies were detected, with a pass rate of only 42.9%. In 2019, Staphylococcus aureus and Klebsiella pneumoniae were detected, with a pass rate of 86.7%. In 2021, Sendai virus antibodies were detected, yielding a pass rate of 85.7%.The pass rate in 2020, 2022, and 2023 was 100%. Rats: In 2017, positive results were found for helminths, mycoplasma antibodies, Staphylococcus aureus, Sendai virus antibodies, murine pneumonia virus antibodies, rat parvovirus RV strain antibodies, rat parvovirus (H-1) strain antibodies, and rat coronavirus antibodies, with a pass rate of 40.0%. In 2019, mycoplasma antibodies, Staphylococcus aureus and Klebsiella pneumoniae were detected, with a pass rate of 35.0%. No positive indicators were detected in 2020. In 2021, Sendai virus antibodies and rat parvovirus RV strain antibodies were detected, with a pass rate of 50.0%. In 2022, positive results for rat parvovirus RV strain antibodies were found, yielding a pass rate of 87.5%. In 2023, Pasteurella pneumotropica and Klebsiella pneumoniae were detected, with a pass rate of 85.7%. Dogs: In 2017 and 2019, the antibody titers for rabies virus and canine distemper virus were below the required standard, with pass rates of 33.3% and 20.0%, respectively. In 2020 and 2022, the pass rate was 100%. Guinea pigs (general grade): In 2019, positive results for Toxoplasma antibodies were detected, with a pass rate of 80.0%. In all other years, the pass rate was 100%. Monkeys: In 2019, positive results for Toxoplasma gondii and rhesus herpesvirus type I antibodies were found, with a pass rate of 87.5%.In 2020 and 2022, rhesus herpesvirus type I antibodies were positively detected, yielding pass rates of 93.3% and 97.5%, respectively. The pass rates in 2021 and 2023 were 100%. Clean guinea pigs, rabbits and pigs all passed the inspection each year.ConclusionIssues related to the parasitic and microbial quality of laboratory animals persist in Sichuan Province. Supervision and sampling inspections have proven to be effective in identifying these issues promptly, serving as a critical measure to ensure the quality of laboratory animals. The results of these inspections offer valuable data to support the healthy development of the laboratory animal industry in Sichuan Province.